Phylogenomic analyses of the genus Drosophila reveals genomic signals of climate adaptation. (8th December 2021) - Li, Fang; Rane, Rahul V.; Luria, Victor; Xiong, Zijun; Chen, Jiawei; Li, Zimai; Catullo, Renee A.; Griffin, Philippa C.; Schiffer, Michele; Pearce, Stephen; Lee, Siu Fai; McElroy, Kerensa; et al.
Abstract: Many Drosophila species differ widely in their distributions and climate niches, making them excellent subjects for evolutionary genomic studies. Here, we have developed a database of high‐quality assemblies for 46 Drosophila species and one closely related Zaprionus . Fifteen of the genomes were newly sequenced, and 20 were improved with additional sequencing. New or improved annotations were generated for all 47 species, assisted by new transcriptomes for 19. Phylogenomic analyses of these data resolved several previously ambiguous relationships, especially in the melanogaster species group. However, it also revealed significant phylogenetic incongruence among genes, mainly in the form of incomplete lineage sorting in the subgenus Sophophora but also including asymmetric introgression in the subgenus Drosophila . Using the phylogeny as a framework and taking into account these incongruences, we then screened the data for genome‐wide signals of adaptation to different climatic niches. First, phylostratigraphy revealed relatively high rates of recent novel gene gain in three temperate pseudoobscura and five desert‐adapted cactophilic mulleri subgroup species. Second, we found differing ratios of nonsynonymous to synonymous substitutions in several hundred orthologues between climate generalists and specialists, with trends for significantly higher ratios for those in tropical and lower ratios for those in temperate‐continental specialists respectively than those in the climate generalists. Finally, resequencing natural populations of 13 species revealed tropics‐restricted species generally had smaller population sizes, lower genome diversity and more deleterious mutations than the more widespread species. We conclude that adaptation to different climates in the genus Drosophila has been associated with large‐scale and multifaceted genomic changes.